THE CORRELATION OF NURSE KNOWLEDGE ABOUT INTERPRETATION OF THE ELECTROCARDIOGRAM WITH THE ACCURACYIN IMPLEMENTING STANDARD PROCEDURE OFOPERATIONALSYNDROME OF ACUTE CORONARYIN INTEGRATED INTENSIVE CARE INSTALLATION ROOMOF SIDOARJOREGIONAL PUBLIC HOSPITAL - Wahyuni, Lutfi; Hidayat, Ahmad (JURNAL KEPERAWATAN SEHAT, 2015)
A professional nurse should be able to interpret the data and the results of the study and thepatient supporting data such as laboratory outcomes and interpret Electro cardiogram (ECG).A skill of nurses in performing the interpretation of ECG results is needed in the handling of cardiovascular distress.The purpose of the research is to know the correlation of nurse knowledge about interpretation of the electrocardiogram with the accuracyin implementing standard procedure of operationalsyndrome of acute coronaryin integrated intensive care installation roomof SidoarjoRegional Public Hospital.This research design used was Analytical Correlational, with cross sectionalapproach. Population in this research were all nurses in the Intensive Care Installation Integrated Hospital Sidoarjo, samples in this study were nurses in ICCU and ECU room of Sidoarjo General Public Hospital, sampling techniques used were purposive Sampling .The majority of respondents knowledge is good that as many as 7 respondents (47%).Most respondents were correct in performing standard operating procedures in patients with Acute Coronary Syndrome as many as 8 respondents (53%).Statistictest used chi square with significance level of ρ = 0.05 obtained0.003 H1unaccepted which means there is no correlation of nurse knowledge about interpretation of the electrocardiogram with the accuracyin implementing standard procedure of operationalsyndrome of acute coronaryin integrated intensive care installation roomof SidoarjoRegional Public Hospital.Implementation of nursing care to emergency room patients used the approach of the nursing process in accordance the emergency priority.It now there has been the development of the nurses role in developing duties from the level of basic nursing towards complexmodern nursing.In the emergency service, Cognitive and Psychomotor are not the only factor affecting the accuracy in implementing emergency action.Keyword : Knowledge, Electro Cardiogram, Accuracy & Acute Coronary Syndrome